2001
DOI: 10.1136/mp.54.4.275
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of the ccn3 (nov) proto-oncogene in human prostate cell lines and tissues

Abstract: (J Clin Pathol: Mol Pathol 2001;54:275-280)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 26 publications
1
52
0
1
Order By: Relevance
“…In Ewing's sarcoma, CCN3 plays a dual role, inhibiting proliferation while promoting migration and invasion of the same cells (Benini et al 2005). In comparison, melanomas overexpressing CCN3 show a higher metastatic potential studied as xenografts (Vallacchi et al 2008), while overexpression of CCN3 in human prostate cell lines (Maillard et al 2001) and high expression in high grade renal cell carcinomas (Glukhova et al 2001) favor an active role in tumorigenesis and progression.…”
Section: Ccn3 (Nov)mentioning
confidence: 99%
“…In Ewing's sarcoma, CCN3 plays a dual role, inhibiting proliferation while promoting migration and invasion of the same cells (Benini et al 2005). In comparison, melanomas overexpressing CCN3 show a higher metastatic potential studied as xenografts (Vallacchi et al 2008), while overexpression of CCN3 in human prostate cell lines (Maillard et al 2001) and high expression in high grade renal cell carcinomas (Glukhova et al 2001) favor an active role in tumorigenesis and progression.…”
Section: Ccn3 (Nov)mentioning
confidence: 99%
“…CCN3 is aberrantly expressed in several malignancies and is associated with the progression of prostate cancer (Maillard et al, 2001), renal cell carcinoma (Glukhova et al, 2001) and Ewing's sarcoma (Manara et al, 2002), whereas in rhabdomyosarcoma and cartilage tumors, CCN3 expression correlates with tumor differentiation. Extensive studies have indicated that the biological properties of CCN3 are dependent upon the cellular context (Perbal et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…CCN3 has also been linked with enhanced metastatic potential for some tumours including Ewings Sarcoma ), osteosarcoma ) and prostate neoplasia (Maillard et al 2001).…”
Section: Introductionmentioning
confidence: 99%